PENGARUH DISIPLIN KERJA DAN PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN PADA PT PIESTA DINAMIKA CONSULT DI JAKARTA SELATAN - Cicih Somantri (Jurnal Menara, 2024)
The purpose of this research is to determine the influence of discipline and career development on employee performance at PT Piesta Dinamika Consult, South Jakarta. The research method used is descriptive research with quantitative analysis. The data used in this research is a survey research method through questionnaires and observation. The population in this study was 118 employees. The sample used the Slovin formula with a difficulty level of 5% so that a sample of 91 people was obtained. Data analysis uses validity tests, coefficient of determination and hypothesis testing. The results of this research show that partially work discipline has a significant effect on employee performance, this is shown by the calculated t value of 3.426 > t table 1.986 and the significant value < 0.05. Partially, career development does not have a significant effect on employee performance, this is shown by the calculated t value of 1.251 < t table 1.986 and a significant value of > 0.05 and work discipline and career development simultaneously have a significant effect on the employee performance of PT Piesta Dinamika Consult South Jakarta . This is shown by the calculated F value > F table or 7.049 > 3.10 and a significant value < 0.05. The R Square value is 0.419, this shows that employee performance is influenced by discipline and career development by 41.9% while the remaining 58.1% is influenced by other factors outside this research